Uniparental disomy screen of Irish rare disorder cohort unmasks homozygous variants of clinical significance in the TMCO1 and PRKRA genes - Molloy, B.; Jones, E. R.; Linhares, N. D.; Buckley, P. G.; Leahy, T. R.; Lynch, B.; Knerr, I.; King, M. D.; Gorman, K. M. (Frontiers in Genetics, 2022)
A uniparental disomy (UPD) screen using whole genome sequencing (WGS) data from 164 trios with rare disorders in the Irish population was performed to identify large runs of homozygosity of uniparental origin that may harbour deleterious recessive variants. Three instances of whole chromosome uniparental isodisomy (UPiD) were identified: one case of maternal isodisomy of chromosome 1 and two cases of paternal isodisomy of chromosome 2. We identified deleterious homozygous variants on isodisomic chromosomes in two probands: a novel p (Glu59ValfsTer20) variant in TMCO1, and a p (Pro222Leu) variant in PRKRA, respectively. The overall prevalence of whole chromosome UPiD in our cohort was 1 in 55 births, compared to 1 in ∼7,500 births in the general population, suggesting a higher frequency of UPiD in rare disease cohorts. As a distinct mechanism underlying homozygosity compared to biallelic inheritance, the identification of UPiD has important implications for family planning and cascade testing. Our study demonstrates that UPD screening may improve diagnostic yields by prioritising UPiD chromosomes during WGS analysis.